Impact of intrafraction motion in pancreatic cancer treatments with MR-guided adaptive radiation therapy - Rusu, Doris N.; Cunningham, Justine M.; Arch, Jacob V.; Chetty, Indrin J.; Parikh, Parag J.; Dolan, Jennifer L. (Frontiers in Oncology, 2023)
Total time of radiation treatment delivery for pancreatic cancer patients with daily online adaptive radiation therapy (ART) on a MR-Linac can range from 50 to 90 minutes. During this period, the target and normal tissues undergo changes due to respiration and physiologic organ motion. We evaluated the dosimetric impact of the intrafraction physiological organ changes. Methods: Ten locally-advanced pancreatic cancer patients were treated with 50 Gy in 5 fractions with intensity-modulated respiratory-gated radiation therapy on a 0.35 T MR-Linac. Patients received both pre-and post-treatment volumetric MRIs for each fraction. Gastrointestinal organs at risk (GI-OARs) were delineated on the pre-treatment MRI during the online ART process and retrospectively on the post-treatment MRI. The treated dose distribution for each adaptive plan was assessed on the post-treatment anatomy. Prescribed dose volume histogram metrics for the scheduled plan on the pretreatment anatomy, the adapted plan on the pre-treatment anatomy, and the adapted plan on posttreatment anatomy were compared to the OAR-defined criteria for adaptation: the volume of the GI-OAR receiving greater than 33 Gy (V33Gy) should be ≤ 1 cubic centimeter. Results: Across the 50 adapted plans for the 10 patients studied, 70% were adapted to meet the duodenum constraint, 74% for the stomach, 12% for the colon, and 48% for the small bowel. Due to intrafraction organ motion, at the time of post-treatment imaging the adaptive criteria was exceeded for the duodenum in 62% of fractions, the stomach in 36%, colon in 10%, and small bowel in 48%. Compared to the scheduled plan, the post-treatment plans showed a decrease in the V33Gy, demonstrating the benefit of plan adaptation for 66% of the fractions for the duodenum, 95% for the stomach, 100% for the colon, and 79% for the small bowel.Post-treatment images demonstrated that over the course of the adaptive plan generation and delivery, the GI-OARs moved from their isotoxic low-dose region and nearer to the dose-escalated high-dose region, exceeding dose-volume constraints. Intrafraction motion can have a significant dosimetric impact, therefore measures to mitigate this motion are needed. Despite consistent intrafraction motion, plan adaptation still provides a dosimetric benefit.